The Psychology of Word Meanings - Schwanenflugel, Paula (Psychology Press, 2013)
This volume contains perspectives from a collection of cognitive scientists on the psychological, philosophical, and educational issues surrounding the meanings of words and how these meanings are learned and accessed. It features chapters covering the nature and structure of word meaning, how new word meanings are acquired in childhood and later on in life, and how research in word processing may tell us something about the way in which word meanings are represented and how they relate to the language processor.
Keywords: Microsoft Office; Word processing; Traitement de texte